Feasibility of building a greenfield contract manufacturing plant - Goertz, Marvin (Kansas State University, 2015)
Bunge is a global agribusiness company that has invested in a facility to produce extruded ingredients and inclusions in its Woodland, California rice mill. Because Bunge is not a branded food manufacturer, it is in a unique position to be a contract manufacturer to a variety of customers without the potential for a conflict of interest. Also, because Bunge is primary in three of the most common ingredients for extruded products, corn, rice and oil, this would be a move down the value chain that would allow it to be more competitive. The initial investment in Woodland has allowed Bunge to learn more about the manufacture of extruded ingredients and inclusions and also gauge overall market demand. A possible next step would be to build a second facility in the eastern half of the United States to expand capacity and be geographically situated to supply the Midwest, South and Northeast regions of the U.S. In order to begin exploring the possibility of a greenfield expansion into the contract manufacture of extruded ingredients and inclusions, this thesis considers three subjects. The first is a customer survey case study, which discovers the customer found high price and whether or not the manufacturer was considered a strategic partner to be the most significant factors in how desirable a manufacturer is. The second subject considered is the ideal location for a second manufacturing site based on a number of factors, including distance from both the customer base and inputs, labor issues, and any savings associated with a particular site. It was found that distance from the ultimate customer may be less important overall than the other factors. The third and final component of the research involved conducting a financial feasibility study. The analyses were conducted under alternative scenarios and subjected to a sensitivity analysis on a number of crucial variables. The weighted average NPV for the alternative scenarios was about $31 million and the IRR of 13.8% cleared the company’s investment hurdle rate. The payback period was estimated to be just under six years. All these suggest that the project as presented in this research is feasible and any investment in it, subject to the absence of any unforeseen event, will be profitable. It is hoped that this information can be used as a starting point and a guide to consider a future investment based on demand and other market indicators available at the time such a decision is required.
Keywords: Economic feasibility; Greenfield; Net present value; Agriculture, General (0473); Management (0454)